CLASSIFICATION AND TYPES OF PERIPHRASES - Abduraxmonova Sayyora Abdumajidovna (Web of Journals Publishing, 2025)
This article is devoted to periphrasis, which are important tool in language that enriches communication, adds depth to expression, and improves understanding. A periphrasis is one of the tools for communication and the use of linguistic periphrasis boosts expressiveness to our conversation and written texts. In this article, we will delve into the types of periphrases in English language and provide examples to differentiate its types clearly.
Keywords: Linguistic periphrasis, phraseological compounds, , expressiveness, logical, figurative rhetoric, analogy.